Evaluation of groundwater and soil pollution in a landfill area using electrical resistivity imaging survey - Ahmed, Abdelatif Mukhtar; Sulaiman, Wan Norazmin (Springer-Verlag New York, 2001)
Landfills are sources of groundwater and soil pollution due to the production of leachate and its migration through refuse. This study was conducted in order to determine the extent of groundwater and soil pollution within and around the landfill of Seri Petaling located in the State of Selangor, Malaysia. The condition of nearby surface water was also determined. An electrical resistivity imaging survey was used to investigate the leachate production within the landfill. Groundwater geochemistry was carried out and chemical analysis of water samples was conducted upstream and downstream of the landfill. Surface water was also analyzed in order to determine its quality. Soil chemical analysis was performed on soil samples taken from different locations within and around the landfill in the vadose zone (unsaturated zone) and below the water table (in the soil saturated zone). The resistivity image along line L-L1 indicated the presence of large zones of decomposed waste bodies saturated with highly conducting leachate. Analysis of trace elements indicated their presence in very low concentrations and did not reflect any sign of heavy metal pollution of ground and surface water or of soil. Major ions represented by Na, K, and Cl were found in anomalous concentrations in the groundwater of the downstream bore hole, where they are 99.1%, 99.2%, and 99.4%, respectively, higher compared to the upstream bore hole. Electrical conductivity (EC) was also found in anomalous concentration downstream. Ca and Mg ions represent the water hardness (which is comparatively high downstream). There is a general trend of pollution towards the downstream area. Sulfates (SO4) and nitrates (NO3) are found in the area in low concentrations, even below the WHO standards for drinking water, but are significantly higher in the surface water compared to the groundwater. Phosphate (PO4) and nitrite (NO2), although present in low levels, are significantly higher at the downstream. There is no significant difference in the amount of fluoride (F) in the different locations. In the soil vadose zone, heavy metals were found to be in their typical normal ranges and within the background concentrations. Soil exchangeable bases were significantly higher in the soil saturated zone compared to the vadose zone, and no significant difference was obtained in the levels of inorganic pollutants. With the exception of Cd, the concentration ranges of all trace elements (Cu, Zn, Cr, Pb, and Ni) of Seri Petaling landfill soils were below the upper limits of baseline concentrations published from different sources.